Toxicodinamia del herbicida Imazetapir en Scenedesmus vacuolatus : efecto de un formulado comercial, sus componentes y la mezcla con glifosato : transferencia en una cadena trófica - Fassiano, Anabella Victoria (2016)
In the last decades rhe use of herbicide from the imidazolinones group and their mixture with glyphosate has increased. These pesticides usually reach water bodies, affecting the organisms that inhabit them, such as microalgaes. Any adverse effect on them can affect organisms in higher trophic levels and even the en tire aquatic ecosystem. The aim of this thesis is to evaluare the impact of imazethapyr, in its different presentations, on aquatic organisms, producers and prima1y consumers, such as the microalgae Scenedesmus vacuohtus (Chlorophyta) and the mussel Limnoperna fartunei (Bivalvia), respectively. Microalgae were exposed to various concentrations of an imazethapyr commercial formulation (Verosil"'), the formulation additives, imazethapyr in the acid form or as ammonium salt and an imazethapyr-glyphosate formulation (OneWay®). Morpho-physiological and oxidative stress parameters were assessed in exposed microalgae and bivalve fed with microalgae exposed to the formulations. Our results show that the toxicity of the Verosil'" formulation is mainly related to the formulation additives and the active ingredient has an enhancing effect. On the other hand, herbicide mixture has a moderare effect on the microalgae. I was proved that oxidative stress participares in the agochemicals toxicity. In mussels fed with microalgae previously exposed to the imazetapir formulation, there has a disturbance in animal physiology and oxidative stress up to 2 weeks of treatment, whereas at longer times (4 and 6 weeks) protection strategies would be activated. In the case of mussels fed with microalgae exposed to the OneWai' formularion, there was an increase in the mortality rate rom 2 weeks of treatment on. Adverse effects found evidence of the environmental hazard posed by these agrochemicals and the need for further studies of additives and mixtures of pesticides and effects on other trophic levels.